THE PEERKADA: KEY TO INCREASE THE STATISTICS AND PROBABILITY PERFORMANCE OF THESENIOR HIGHSCHOOL STUDENTS - QUITOLA, ELIZABETH (International Journal of Business, Law, and Education, 2022)
Abstract This study investigated the effect of peer tutoring strategy to the academic performance of Grade 11 students in Statistics and Probability during the 2nd semester of School Year 2018 – 2019 at the Isabela School of Arts and Trades – Main. Specifically, it attempted to determine and compare the performance of the students before and after their exposure to the intervention. This research used experimental method. The semestral grades were the main data used in this study. The results revealed that the performance of the respondents after the intervention were significantly higher than before their exposure to the intervention. Based on the findings, there was an increase in the performance of Grade 11 students in using Peer Tutorial. It is recommended that teachers teaching mathematics should use Peer Tutorial when teaching lessons in Statistics and Probability. Furthermore, a similar study should be conducted to further test the effectiveness of Peer Tutorial.